Penyuluhan Pencegahan Bullying di SDN 106831 Bakaran Batu Lubuk Pakam - Wasiyem; Hafizah Siti Fathimah; Puan Maulida Syifa Rizqi; Putri Aulia Ramadhani; Rini Alvionita; Riska Ananda; Wuni Barokah (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2024)
This social and cultural counseling was carried out at one of the elementary schools in Lubuk Pakam with the theme of Bullying Prevention. This outreach effort was carried out to ensure that students at elementary schools, namely SDN 106831 Bakaran Batu, can apply the messages and information that have been conveyed, in this way it is hoped that it can reduce the number of victims related to bullying cases which always end in death.  The word bullying, which comes from the English word 'bull', means a bull that likes to gore, and has recently become an interesting topic of discussion.  Bullying behavior occurs in various places, starting from educational or school environments, workplaces, homes, neighbors, playgrounds, and so on.  Bullying has a broad and serious impact on children who are victims. These impacts include physical and mental health problems, such as depression, anxiety, sleep problems, and decreased enthusiasm for learning.  Children who experience bullying can also feel unsafe in the school environment.  Victims of acute bullying do not rule out the possibility of causing death. This counseling is carried out using the Lecture Method which aims to explain an idea, understanding, or message orally to a target group so that they obtain the desired information.